Exploratory assessment of an endolaryngeal surgical model with a novel hyperangulated 3D printed laryngoscope - Hahn, Viola; Gschwend, Gabriel L.; Kienle, Linus L.; Schild, Leon R.; Greve, Jens; Hoffmann, Thomas K.; Schuler, Patrick; Böhm, Felix (European archives of oto-rhino-laryngology and head & neck, 2025)
Objective: This study introduces a hybrid training model for endolaryngeal surgeries integrating a porcine larynx into a plastic airway manikin. The study explores interventions with a conventional rigid laryngoscope as well as with the novel hyperangulated laryngoscope for surgery (sMAC). Methods: We integrated a porcine larynx into a plastic airway manikin with blue markings on vocal folds simulating lesions and utilized a conventional rigid laryngoscope and the sMAC for endolaryngeal cordectomies and biopsies. Results: The setup provided clear visual exposure of the glottic plane, enabling precise surgical interventions. Trained surgeons and residents successfully performed cordectomies and biopsies on the model. Conclusion: The hybrid model offers a realistic, cost-effective solution for training and testing endolaryngeal surgical procedures, particularly with the sMAC. Despite anatomical differences between porcine and human larynges, the model’s affordability and tissue similarity render it a valuable training tool. Further studies are warranted to evaluate its efficacy for training.